Gender differences, academic patenting, and tenure-track reform in China: Evidence from life sciences at elite universities. - Xin Zhang; Shi Chen; Wei Zheng (PLoS ONE, 2024)
This study is the first to examine the gender gap in academic patenting among faculty members in Chinese universities, a critical issue for the sustainable development of scientific research and innovation. Using a unique dataset that includes the patenting activities and professional status of 1,836 faculty members in life science-related departments at 36 top Chinese universities, this research reveals an evolving landscape of patenting dynamics. The trend of male faculty members leading in the annual number of patent applications and patents granted has shifted among newly graduated faculty members. Female faculty submit and receive their first patent applications significantly earlier than male faculty. However, male faculty are more likely to be lead inventors, and this gender gap remains difficult to close, with female faculty more likely to be supporting inventors. This research is contextualized within the broader framework of China's university tenure reform and the growing presence of women in the life sciences. While progress is evident, the study uncovers persistent systemic barriers that prevent women from fully translating their research into patentable innovations. By identifying these social and institutional barriers, our study not only sheds light on the gender gap, but also suggests policy measures to promote gender equity in scientific innovation, making it a critical read for policymakers and academic leaders.